A controller design used in Lorenz synchronization chaotic system for secure communication based on LMI fuzzy control system - Domingues, P. E.; Righeto, E.; Teixeira, MCM; Oki, N. (Institute of Electrical and Electronics Engineers (IEEE), 2003)
This paper describes a mathematical study about chaotic system and about the unified approach of chaos control via fuzzy control system based in Linear Matrix Inequality to design a controller which synchronizes the transmission/reception system. This system, that was based in Lorenz chaotic circuit, can be used for transmit signals in secure way.